2020
DOI: 10.1002/biot.201900565
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Omics Reveals Impact of Cysteine Feed Concentration and Resulting Redox Imbalance on Cellular Energy Metabolism and Specific Productivity in CHO Cell Bioprocessing

Abstract: Chinese hamster ovary (CHO) cells are currently the primary host cell lines used in biotherapeutic manufacturing of monoclonal antibodies (mAbs) and other biopharmaceuticals. Cellular energy metabolism and endoplasmic reticulum (ER) stress are known to greatly impact cell growth, viability, and specific productivity of a biotherapeutic; but the molecular mechanisms are not fully understood. The authors previously employed multi‐omics profiling to investigate the impact of a reduction in cysteine (Cys) feed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
5
18
0
Order By: Relevance
“…Cysteine is an important substrate for synthesis of antioxidants, including taurine and glutathione (GSH), which support high rates of oxidative phosphorylation associated with high-qP cells. A recent study found that a depletion of cysteine in CHO cell culture medium negatively impacted VCD, viability, and qP, and attributed these observations to redox imbalance, endoplasmic reticulum stress, and mitochondrial dysfunction [46]. The accumulation we observed in high-qP cells could reflect the ability of these cells to supplement feed cysteine with endogenous production.…”
Section: Aspartic Acid and Cystinesupporting
confidence: 49%
“…Cysteine is an important substrate for synthesis of antioxidants, including taurine and glutathione (GSH), which support high rates of oxidative phosphorylation associated with high-qP cells. A recent study found that a depletion of cysteine in CHO cell culture medium negatively impacted VCD, viability, and qP, and attributed these observations to redox imbalance, endoplasmic reticulum stress, and mitochondrial dysfunction [46]. The accumulation we observed in high-qP cells could reflect the ability of these cells to supplement feed cysteine with endogenous production.…”
Section: Aspartic Acid and Cystinesupporting
confidence: 49%
“…Recently, Lakshmanan et al (2019) employed transcriptomic and proteomic profiling to systematically link phenotypic differences, including cell growth and glycosylation, with genotypes across different CHO hosts [16]. Ali et al (2019 and2020) conducted omics studies to explore the impact of cysteine feed level on CHO cell metabolism [17,18]. Additionally, omics approaches have been applied to support scale-up activities.…”
Section: Introductionmentioning
confidence: 99%
“…Even though expression was not increased for the chaperone proteins measured, a significant upregulation of BAK1 and Caspase-3 was observed indicating ER stress. While it would need additional experiments to verify our findings on the level of protein expression, it seems that in both cases, lowering the pH has beneficial effects on maintaining redox balance which is ultimately favoring recombinant protein expression (Ali et al, 2019(Ali et al, , 2020. Generally, combining the proteome analysis with additional omics-data, such as metabolomics or phosphoproteomics, would be beneficial to allow for a deeper biological interpretation even though it increases the experimental effort and time.…”
Section: Improved Mab Productivity Of Cells At Low Ph Is Due To Improved Energy Metabolismmentioning
confidence: 89%
“…Nevertheless, there is still limited knowledge about of how these process alterations affect fundamental biological processes within the production cells and how these alterations ultimately relate to quality attributes such as, e.g., charge variants which could alter product efficacy and safety (Torkashvand and Vaziri, 2017;Papathanasiou and Kontoravdi, 2020). For this reason 'omics techniques have been applied to explore CHO cells under various conditions in order to provide a foundation for knowledge-driven improvements of manufacturing processes (Baycin-Hizal et al, 2012;Farrell et al, 2014;Heffner et al, 2017;Stolfa et al, 2018;Ali et al, 2019Ali et al, , 2020Lakshmanan et al, 2019). More accurate and complete genome references (Rupp et al, 2018) in combination with technological improvements in analytical instrumentation (Williamson et al, 2016) now enable proteomic profiling of CHO cells to a depth and accuracy that was previously not possible.…”
Section: Introductionmentioning
confidence: 99%